Yield potential trends of tropical rice since the release of IR8 and the challenge of increasing rice yield potential - Peng, S.; Cassman, K.G.; Virmani, S.S.; Sheehy, J.E.; Khush, G.S. (Wiley, 1999)
Since the release of IR8 in 1966, 42 additional indica rice (Oryza sativa L.) cultivars developed by the International Rice Research Institute (IRRI) for the irrigated and favorable rainfed lowlands have been released in the Philippines. The maximum yield of IR8 has been reduced by about 2 Mg ha−1 during the past 30 yr. Empirical breeding for population improvement within the indica germplasm has resulted in the maintenance of rice yield potential in the tropics of about 10 Mg ha−1. To break the yield barrier, several approaches are being explored. These include development of a new plant type (NPT) with low tillering capacity and large panicles from tropical japonica germplasm and exploitation of heterosis through intervarietal and intersubspecific hybrids. Hybrid rice between indicas increased yield potential by about 9% under the tropical conditions. The higher yield potential of indica/indica hybrids compared with indica inbred cultivars was attributed to the greater biomass production rather than harvest index. New plant type breeding has not yet improved yield potential due to poor grain filling and low biomass production. Factors that cause poor grain filling and low biomass production of the NPT lines have been identified. Selecting parents with good grain filling traits, introduction of indica genes into NPT's tropical japonica background, and a refinement of the original NPT design are expected to improve the performance of the NPT lines. Further enhancement in yield potential may be possible from use of intersubspecific heterosis between indica and NPT lines.